Informal commercial importers in the Caribbean : evidence from Trinidad and Tobago and Guyana - Hosein, Roger (2012)
Attempts a micro based study to profile informal commercial importers (ICIs) operating between Trinidad and Tobago and Guyana. Offers some policy recommendations aimed at incorporating ICIs into the formal economy.